Effects of Ignatia amara in mouse behavioural models - Marzotto, Marta; Conforti, Anita; Magnani, Paolo; Zanolin, Maria Elisabetta; Bellavite, Paolo (Homeopathy, 2012)
Background:Ignatia amara (Ignatia), a remedy made from the Strychnos ignatii seeds, is used for anxiety-related symptoms, but consistent evidence of its activity in reproducible experimental models is lacking. An investigation was performed in order to assess on mice, by means of emotional response models, the activity of homeopathic Ignatia dilutions/dynamizations.Methods: Groups of 8 mice of the CD1 albino strain were treated intraperitoneally for 9 days with 0.3 ml of five centesimal (C) dilutions/dynamizations of Ignatia (4C, 5C, 7C, 9C and 30C). Control mice were treated with the same hydroalcoholic (0.3%) solution used to dilute the medicines. Diazepam (1 mg/kg) was the positive reference drug. Validated test models for locomotion and emotional response, the Open-Field (OF) and the Light–Dark (LD) tests, were employed. Five replications of the same protocol were carried out, in a randomised way using coded drugs/controls.Results: In the OF the general locomotion of mice was slightly decreased by Ignatia 4C, but not by Ignatia 5C, 7C, 9C and 30C, indicating the absence of unspecific motor impairment or sedation by these dilutions/dynamizations. Ignatia and diazepam seemed to decrease the number of urine spots released in the OF during 10 min, with borderline significance (P=0.083). In the LD the tested medicine showed anxiolytic-like activity (increase of time spent and distance travelled in the lit area), though to a lesser extent than diazepam. The highest and most significant difference with untreated controls (P < 0.01) was observed with the 9C dilution/dynamization. Among the 5 replication experiments, the best drug effects were obtained where the baseline anxiety of mice was higher.Conclusions: Homeopathic Ignatia dilutions/dynamizations (peak at 9C) modify some emotion-related symptoms in laboratory mice without affecting locomotion.
Keywords: Strychnos Ignatii; Ignatia; Strychnine; Animal models of anxiety; Open-Field test; Light–Dark test; Homeopathic dilutions/dynamizations; Nanopharmacology